1987
DOI: 10.1190/1.1442362
|View full text |Cite
|
Sign up to set email alerts
|

Near‐infrared detection of ammonium minerals

Abstract: Diagnostic near‐infrared spectral features have been identified for minerals with ammonium [Formula: see text] bound in the crystal structure. Spectral bands near 2.12, 2.02, and 1.56 μm are characteristic of synthetic and natural [Formula: see text] minerals. Laboratory spectra of [Formula: see text] minerals are distinct from spectra of OH‐bearing minerals and have diagnostic shifts in band position among different mineral types. [Formula: see text] minerals were detected at several mineralized hot‐spring de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…The absorption features observed in these minerals between 400 and 2500 nm must be overtones and combinations of these features. Ammonium minerals such as the sal ammoniac are also found in playas (Sonnenfeld 1984), and also have absorption features in this region (Krohn and Altaner 1987).…”
Section: Resultsmentioning
confidence: 99%
“…The absorption features observed in these minerals between 400 and 2500 nm must be overtones and combinations of these features. Ammonium minerals such as the sal ammoniac are also found in playas (Sonnenfeld 1984), and also have absorption features in this region (Krohn and Altaner 1987).…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that hydrothermal alteration can result in ammonium-enrichment of a variety of rock types (Krohn and Altaner 1987, Hall 1988a, Appleton et al 1988. Basaltic magmas normally have very low ammonium contents, but the pro cess of spilitic alteration involves interaction with large volumes of hydrothermal fluid, so there is a possibility that basalts could acquire ad ditional ammonium from their surroundings dur ing the course of hydrothermal alteration.…”
Section: Introductionmentioning
confidence: 99%
“…The ammonium content of granitic magmas is therefore of considerable petrogenetic interest. However, the ammonium ion is very easily mobilised by hydrothermal activity (Krohn and Altaner, 1987;Ridgway et al, 1990;Hall et al, 1991), andin a granite that has undergone hydrothermal alteration it may be difficult to distinguish primary ammonium from secondary ammonium. Because ammonium is an important constituent of hydrothermal systems, but only a trace constituent of igneous rocks, the ammonium content of the latter may be significantly modified by a degree of alteration which is too small to have a noticeable effect on the major element chemistry of the rock.…”
mentioning
confidence: 99%